A Proposed National Surveying And Mapping Policy In Nepal - Adhikary, Krishna Raj; Paudyal, Dev Raj (Journal on Geoinformatics, Nepal, 2007)
The political objective of Nepal is poverty reduction and sustainable development. The sustainable land administration and management is a tool to achieve the political objectives. From an institutional perspective, land administration and management includes the formulation of land policy, the legal framework, resource management, land administration arrangements, and land information management. In Nepal, The draft of National Land Policy document has been formulated and it is under discussion at ministerial level. One of the recommendations on that National Land Policy document is the formulation of National Surveying and Mapping Policy. It is realized that the time has come to formulate the "National Surveying and Mapping Policy" based on the proposed National Land Policy document in keeping abreast of development and changes in the global technological environment. In this paper, an attempt has made to prepare National Surveying and Mapping Policy in Nepal. The main issues and challenges are also raised on this paper to formulate the National Surveying and Mapping Policy in Nepal. This paper starts with Background and describes the background for developing this policy document. It then describes about Survey Department activities. It then elaborates the policy on Surveying and Mapping in Nepal with policy on Geodetic Surveys and Space Science, Topographic Survey and Geographical Information Infrastructure, Cadastral Survey and Land Information, Research & Development, Resource, Administration. Finally, it concludes with some concluding remarks.